PERBANDINGAN PENGGUNAAN PLTS DENGAN GENSET DI DESA SOKO KEMBANG KECAMATAN PETUNGKRIYONO KABUPATEN PEKALONGAN DITINJAU DARI MORE EFFICIENT PROCESS - Ghoni Musyahar (Elkom : Jurnal Elektronika dan Komputer, 2019)
In Pekalongan, precisely in the village of Soko Kembang, Petungkriyono sub-district, as many as 31 units of PLTS were made. This PLTS works stand alone, with the SHS system. Each SHS unit consists of a 50 Wp solar panel, three light points, a 70Ah battery, and a Box Control Unit. Based on preliminary field studies, the use of SHS is very useful and helps the community at night especially students and mothers who have small children and helping residents of Soko Kembang village, a remote village that had previously relied on lighting from oil lamps and rental generators. The use of solar power plants has an impact on the economic life of the community, which is assessed from an increase in the people's economy. This is evidenced by the high payback.